Saturation throughput analysis of IEEE 802.11 DCF with heterogeneous node transmit powers and capture effect. (2017) - Lei, Lei; Zhang, Ting; Zhou, Liang; Song, Xiaoqin; Cai, Shengsuo
The transmit power control schemes allow the wireless nodes to select a minimum required transmit power from all available power levels to access the medium. In this paper, we focus on analysing the saturation throughput performance of IEEE 802.11 DCF networks with heterogeneous node transmit power levels and the capture effect. We first analyse the capture effect among packets sent at different power levels and derive the analytical expression of the capture probability. Then, we propose a three-dimensional Markov chain to model the backoff procedure performed by a tagged sending node under the condition of heterogeneous transmit power levels, and compute the total saturation throughput of the network with the previously derived capture probability. Finally, we validate the accuracy of our model by comparing the analytical results with the simulation results, and analyse the impact of the capture effect on the saturation throughput performance of IEEE 802.11 DCF networks.